2014
DOI: 10.3390/rs6053906
|View full text |Cite
|
Sign up to set email alerts
|

Change Detection of Tree Biomass with Terrestrial Laser Scanning and Quantitative Structure Modelling

Abstract: Abstract:We present a new application of terrestrial laser scanning and mathematical modelling for the quantitative change detection of tree biomass, volume, and structure. We investigate the feasibility of the approach with two case studies on trees, assess the accuracy with laboratory reference measurements, and identify the main sources of error, and the ways to mitigate their effect on the results. We show that the changes in the tree branching structure can be reproduced with about ±10% accuracy. As the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 29 publications
2
80
0
Order By: Relevance
“…The average volume error for all models was below 5%, and using, e.g., the circular cylinder model on extremely elliptic stems, resulted in a maximum volume error below 14%. These ties well with the field-calibrated studies of [16,23], as the volume and length errors are similar in all studies. In [16], it is shown that a hybrid version of polyhedral and cylindrical modelling is accurate, even for the highly complex shapes of stump-root systems.…”
Section: Discussionsupporting
confidence: 66%
“…The average volume error for all models was below 5%, and using, e.g., the circular cylinder model on extremely elliptic stems, resulted in a maximum volume error below 14%. These ties well with the field-calibrated studies of [16,23], as the volume and length errors are similar in all studies. In [16], it is shown that a hybrid version of polyhedral and cylindrical modelling is accurate, even for the highly complex shapes of stump-root systems.…”
Section: Discussionsupporting
confidence: 66%
“…Finally, the distribution of wood volume in the canopy cannot be calculated using allometric equations. Branch properties, tree crown structure, and canopy space filling are key characteristics in understanding light-use efficiency and tree-tree interactions [7,8], and thus the dynamics in multiple service forests. To obtain this information by direct field measurement is, however, challenging and time-consuming, and therefore costly [9].…”
Section: Introductionmentioning
confidence: 99%
“…Terrestrial Laser Scanning (TLS) provides a ground based way to estimate the biomass of trees and shrubs. Three dimensional (3D) point clouds of the vegetation surface are derived from laser scans and allow the reconstruction of quantitative 3D vegetation models [14][15][16] that, with knowledge of the vegetation density, enable biomass estimation without allometric information [17,18]. Most TLS studies have focused on woody vegetation, although studies have used TLS for assessing grass height, including the change in height associated with grazing [19] and fire [20,21], as well as for estimating the AGB of crops [22,23].…”
Section: Introductionmentioning
confidence: 99%